2022
DOI: 10.5423/ppj.oa.05.2022.0064
|View full text |Cite
|
Sign up to set email alerts
|

Culturable Endophytes Associated with Soybean Seeds and Their Potential for Suppressing Seed-Borne Pathogens

Abstract: Seed-borne pathogens in crops reduce the seed germination rate and hamper seedling growth, leading to significant yield loss. Due to the growing concerns about environmental damage and the development of resistance to agrochemicals among pathogen populations, there is a strong demand for eco-friendly alternatives to synthetic chemicals in agriculture. It has been well established during the last few decades that plant seeds harbor diverse microbes, some of which are vertically transmitted and important for pla… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
12
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 34 publications
0
12
0
Order By: Relevance
“…Fungal endophyte genera such as Cladosporium, Alternaria, Diaporthe, and Epicoccum were isolated previously from soybean stems (Impullitti and Malvick 2013). In addition, Kim et al (2022) reported that culturable endophyte microbes that inhabit soybean seeds may have a potential role for inhibiting seed-borne pathogens. They also suggested that fungal endophytes isolated from soybean seeds, such as Alternaria hungarica and Clasdosporium pseudocladosporioides, have suppressive effects against seed-borne pathogens.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Fungal endophyte genera such as Cladosporium, Alternaria, Diaporthe, and Epicoccum were isolated previously from soybean stems (Impullitti and Malvick 2013). In addition, Kim et al (2022) reported that culturable endophyte microbes that inhabit soybean seeds may have a potential role for inhibiting seed-borne pathogens. They also suggested that fungal endophytes isolated from soybean seeds, such as Alternaria hungarica and Clasdosporium pseudocladosporioides, have suppressive effects against seed-borne pathogens.…”
Section: Discussionmentioning
confidence: 99%
“…Introduction of Paraburkholderia phytofirmans PsJN to wheat showed changes in seed microbiome composition and plant growth traits (Mitter et al 2017). During the stages from seed germination to seedling, seed endophytes are the first to associate with plants before other microbial invasions from the soil (Kim et al 2022). Johnston-Monje et al (2021) recently proved that both seedtransmitted bacteria and fungi can have a long-term effect on crop microbiome structure affecting plant growth, health, and productivity.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Recent data on multiple cultivated species indicate that the seed microbiota would constitute most cultivated plants' microbial populations [17]. The study of seed-borne endophytes has focused on shortcycle crops (e.g., maize, soybean, rice) where the effect of endophytes on establishment, growth, and resistance to stresses has been evaluated [26] [27][28] [29]. For tropical perennial plants, studies on the association and interaction of plants and seed-borne microbiota are still incipient.…”
Section: Introductionmentioning
confidence: 99%
“…Current studies on the soybean seed microbiome indicated lower diversity compared to rhizosphere and phyllosphere microbiomes [34]. Using culture-dependent and culture-independent methods, 22 and 27 bacterial genera were identified in the soybean seed microbiome, respectively [35, 36]. Among these seed-associated microbes, Bacillus , Pantoea , and Sphingomonas were identified as the most dominant genera in soybean seeds [36], and some of these seed-associated bacteria exhibited in vitro antagonistic activity against various soybean pathogens [35].…”
Section: Introductionmentioning
confidence: 99%